A new species of Paracapnia from California (Plecoptera: Capniidae) - Kondratieff, Boris C. (Illiesia, 2010)
Paracapnia baumanni sp. n. is described from northern California. The apterousnew species is related to P. humboldta and P. boris by sharing the mesosternal postfurcasternal plates separated from the spinasternum, but the epiproct of the new species is shorter, widest in the middle, and lacking an upturned tip and the female abdominal terga are completely sclerotized.
Keywords: Capniidae; entomology; new species; Paracapnia; Plecoptera